A logística de transporte e as cadeias agropecuárias avícola e suinícola, impacto social e econômico no desenvolvimento local do município de Toledo - PR - Manfroi, Armando Staudt (2008)
The economy in the west of the State of Paraná is market by the strong participation of the agricultural activities; much from what is produced either in the State or in the country is native of this region. Particularly for the Municipality of Toledo, the aviculture and swine culture are the main agricultural. These are directly mediated by the activities of transport logistics, which play the important and directly responsible role by the appropriate development of the agricultural. Thus, this search shows the development of a model which aims to measure the impacts caused by the transport logistics in the aviculture and swine culture. Thus, it has been attempted to answer what the economical and social impacts are that the transport logistics cause on birds and swine chains, that justified by the characteristic of importance which the transport activity has for the activities, due to the fact that it is treated of an activity that provides the connection among several initial productive stages. The data collection has contemplated the search for information in local public organs and private companies which are directly connected to the activity; this information were fundamental to the is referred to the construction of indicators about the studied activities. From the collected data, it has been developed a matrix of analysis from this data which shows the direct relation among the global numbers in the Municipality (e.g., the total of employment in the Municipality in relation to the total employment from the bird and swine chains). It has been evident during the search the essential role of the transport logistics, and it can be claimed that there is a high level of dependence of the activities that involve bird and swine production in the transport logistical services, thus, any alteration in the transport configuration may bring direct consequences to aviculture and swine culture, interfering in the results and in the production. It is believed that this study has contributed to the explanation of the importance of the transport activities in the context of birds and swine production for the Municipality, and indirectly for the local economical and social development.